Migrants access to the labour market and ethnic niching: case study of Zimbabweans employed in the Cape Town restaurant industry - Silubonde, Tikwiza Rayleen (Department of Sociology, 2014)
This research used a qualitative method of enquiry to examine observations and theoretical claims made about the ability of migrants to secure employment. These claims indicated that migrants of the same ethnic groups are able to enter into the job market of their countries of residence, to the extent that they become concentrated in specific industries. The ethnic niche theory, the segmented labour theory and social network theories were taken as the point of departure. These theories were further broken down into four key factors that were believed to be integral to understanding how migrants gain entry and consolidate themselves in different industries. The key factors identified were job search methods, social and family networks, recruitment/employer practices and migrants characteristics. A case study approach focusing on interviews with employees, managers and owner in the Cape Town was used to examine how the different factors contribute to the process of how migrants secure employment. Face to face Interviews were conducted with five male respondents, and comprised open-ended questions. Questions covered the migrants, personal and educational background, migration and employment history, social activities and residential location. The findings confirmed network theory claims that Migrants have been able to use the social capital gained from their social and family networks, to benefit from job related information and access to jobs through referrals and vouching. It was also found that as argued by the segmented labour theory, jobs are differentiated into different sectors, and migrants are more likely to secure employment in the secondary sector. Moreover, as suggested by the ethnic niche theory, migrants did become concentrated in specific sectors as a result of networks and the use of methods such as referral hiring. An important finding that emerged was that while social and family networks play a major role in the creation and maintaining of ethnic niches, there are other contributing factors. Significantly, the structural and institutional context in the host country also plays a major role in the insertion of migrants into specific industries. This goes further than segmented labour theory analysis, which stops at how jobs are differentiated in the market, to acknowledge the role played by the context of the specific industry, the state of the local labour market and the immigration legislation. It was found that it is beneficial to use theory in conjunction with the case context and immigrant characteristics. Thus a multidimensional approach focusing on job search methods, social and family networks, recruitment/employer practices and migrants characteristics is required to understand migrants, access to employment.